Fungi Isolated from Cockroach (Periplaneta americana ) Preserved in the Department of Plant Protection Insect Museum - Hamed, Fathia saeid; El-Gali, Zahra Ibrahim (Al-Mukhtar Journal of Sciences, 2021)
This study was conducted to isolate and identify fungi associated with the cockroach Periplaneta americana L. (Orthroptera: Blattidae) which was taken from the Insect Museum of the Plant Protection Department, Faculty of Agriculture, Omar Al-Mukhtar University, El-Bayda, Libya. Ten insects were collected from insect specimen boxes containing naphthalene crystals. The insects were separated into their parts, legs, wings, antennae, and mouthparts, superficially sterilized, and incubated on PSA nutrient medium. Eight species of fungi were isolated. The identified fungal isolates include Alternaria altemata, Aspergillus niger, A. terreus, Beauvaria sp., Madurella sp., Penicillium verrucosum, P. commune, Penicillum sp. It was carried on parts of the insect’s body, the study also showed that A. niger was the most common fungi isolated with a frequency of 23.8% and the percentage reached 41.7%, followed by A. altemata and P. verrucosum with a frequency of 9.5% and 7.1%, and the percentage was 16.7% and 12.7% for both fungi respectively, and the lowest density was for A. terreus, Beauvaria sp. which reached 8.3%. From this study, it was concluded that the isolated fungi are storage fungi that attack insects preserved in museums, exposing them to damage.